Prevalence of overweight/obesity and its association with fast food consumption among adolescents in Southern Ethiopia, 2022: a community-based cross-sectional study - Elias, Chernet; Abraham, Awoke; Asrat, Chernet; Yakob, Tagese; Girma, Daniel (Frontiers in Nutrition, 2025)
Overweight and obesity are body mass index (BMI) for age Z-score > +1SD and > +2SD, respectively. Despite its largest contribution to overweight/obesity, there is little attention in our country about fast-food consumption. Hence, this study aimed to assess the prevalence of overweight/obesity and its association with fast-food consumption among adolescents in Southern Ethiopia. From 14 June 2022 to 15 July 2022, a cross-sectional study design was conducted using a structured questionnaire and anthropometric measurements, with a sample size of 563. The data were coded, cleaned, and imported into EPI-INF version 7.2 before being exported to SPSS version 25 for analysis. All variables with p-values less than or equal to 0.25 in bivariate logistic regression were candidate variables for multivariable logistic regression. The response rate of this study was 97%. Based on BMI, the combined prevalence of overweight/obesity was 6.0% (95% CI: 4.2–8.4%). Adolescents who are female, come from high-income families, and eat fast-food frequently are more likely to be overweight or obese. Future health initiatives aimed at lowering the prevalence of overweight and obesity in adolescents should pay special attention to female adolescents and those from high-income families.